A scoping review and prevalence analysis of soil-transmitted helminth infections in Honduras. - Ana Lourdes Sanchez; José Antonio Gabrie; María Mercedes Rueda; Rosa Elena Mejia; Maria Elena Bottazzi; Maritza Canales (PLoS Neglected Tropical Diseases)
Background Honduras is endemic for soil-transmitted helminth (STH) infections, but critical information gaps still remain on the prevalence and intensity of these infections as well as on their spatial distribution at subnational levels. Objectives Firstly, to review the research activity on STH infections in Honduras and secondly, to carry out a national prevalence analysis and map the geographical distribution of these infections in children. Methods A systematic search was conducted of the published and grey literature to identify scientific work on the impact and prevalence of STH infections done between May 1930 and June 30, 2012. International databases and Honduran journals were searched. Grey literature was gleaned from local libraries and key informants. Select studies conducted between 2001 and 2012 were used to produce prevalence maps and to investigate association between STH prevalence and socio-economic and environmental factors. Results Of 257 identified studies, 211 (21.4% peer-reviewed) were retained for analysis and categorized as clinical research (10.9%), treatment efficacy studies (8.1%) or epidemiological studies (81%). Prevalence analysis and geographical mapping included 36 epidemiological studies from Honduras's 18 departments and 23% of its municipalities. Overall STH prevalence was >50% in 40.6% of municipalities. Prevalences above 20% for each trichuriasis, ascariasis, and hookworm infection were found in 68%, 47.8%, and 7.2% of studied municipalities, respectively. Municipalities with lower human development index, less access to of potable water, and with higher annual precipitation showed higher STH prevalences. Conclusions This is the first study to provide a comprehensive historic review of STH research activity and prevalence in Honduras, revealing important knowledge gaps related to infection risk factors, disease burden, and anti-parasitic drug efficacy, among others. Our decade-long prevalence analysis reveals geographical differences in STH prevalence and these findings suggest that differential intervention strategies might be necessary in Honduras for the control of these infections.